Feasibility, Effectiveness and Safety of Prehospital Intravenous Bolus Dose Nitroglycerin in Patients with Acute Pulmonary Edema. (1st November 2020) - Patrick, Casey; Ward, Brad; Anderson, Jordan; Rogers Keene, Kelly; Adams, Elizabeth; Cash, Rebecca E.; Panchal, Ashish R.; Dickson, Robert
Abstract: Introduction: The necessity of rapid preload and afterload reduction in patients with decompensated congestive heart failure (CHF) and acute pulmonary edema (APE) is well established. In the hospital setting, intravenous (IV) nitroglycerin demonstrates improved patient morbidity and mortality. However, prehospital treatment is typically limited to sublingual nitroglycerin at doses that often do not affect afterload. In this study, we assessed feasibility, safety and effectiveness of prehospital IV bolus nitroglycerin in decompensated CHF patients with APE. Methods: This was a retrospective chart review of all emergency medical services (EMS) and ED patient care records of subjects treated for presumed decompensated CHF with APE with bolus-dose IV nitroglycerin between March 15, 2018 and March 15, 2019 by a large, suburban, county-based EMS service in Texas. Inclusion criteria for treatment included both hypertension (systolic blood pressure [SBP] > 160 mmHg) and acute respiratory distress with a paramedic clinical impression of decompensated CHF with APE. Treatment consisted of a 1 mg nitroglycerin bolus, repeated in 5 minutes if SBP > 160 mmHg. Results: During the study period, 48 patients were treated with IV bolus nitroglycerin. Initially, the median (IQR) SBP was 211.0 mmHg (190.0–229.5), 5-minutes post IV NTG was 177.0 mmHg (155.0–199.0), and upon ED arrival was 181.5 mmHg (157.0–207.0). 5 minutes after IV nitroglycerin, the median pulse decreased from 113 (96–124) to 103 (85–117) beats per minute and the median oxygen saturation increased from 86% (74–89) to 98% (96–99). Based on hospital records review, 45/48 (94%) of patients treated with IV nitroglycerin were found to have CHF with APE. A single episode of transient hypotension, which resolved without treatment, did occur during EMS transport. Conclusion : This case series found that patients who were treated by paramedics with IV NTG had improved systolic blood pressure and oxygen saturation upon ED arrival as compared to their initial presentation. Over 90% of these patients were correctly identified by paramedics as having CHF with APE based on ED evaluation. Only one patient had an adverse event, which was transient hypotension that did not require intervention.